1996
DOI: 10.1101/gad.10.13.1569
|View full text |Cite
|
Sign up to set email alerts
|

SR proteins and splicing control.

Abstract: Twenty years have passed since the discovery of premRNA sphcing (for review, see Sharp 1994). The studies leading to this discovery were carried out on the adeno virus late transcript, which undergoes complex alterna tive splicing, and, therefore, the concept of alternative splicing is also 20 years old. In the intervening time, intervening sequences, or introns, have been found in a vast majority of higher eukaryotic genes, and a large frac tion of intron-containing transcripts have been shown to be subject t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
529
0
9

Year Published

1998
1998
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 635 publications
(547 citation statements)
references
References 87 publications
9
529
0
9
Order By: Relevance
“…The N1 exon contains a purine-rich element similar to sequences known to act as splicing enhancers in other exons (Manley & Tacke, 1996;Caceres & Krainer, 1997;Hertel et al+, 1997 …”
Section: The N1 Exon 39 Splice Site Inhibits Splicing Induced By the mentioning
confidence: 99%
See 1 more Smart Citation
“…The N1 exon contains a purine-rich element similar to sequences known to act as splicing enhancers in other exons (Manley & Tacke, 1996;Caceres & Krainer, 1997;Hertel et al+, 1997 …”
Section: The N1 Exon 39 Splice Site Inhibits Splicing Induced By the mentioning
confidence: 99%
“…Alternative pre-mRNA splicing is a common means of gene regulation in eukaryotes that allows the generation of multiple protein isoforms from a single gene (for reviews see Wang & Manley, 1997;Y+ Wang et al+, 1997)+ The control of pre-mRNA splicing pattern can be very precise and there are many examples of exons in mammalian cells whose inclusion is highly tissue specific+ A variety of pre-mRNA sequence elements and regulatory proteins are known to affect the splicing patterns of different RNA transcripts+ Although these regulatory components must ultimately alter spliceosome assembly at certain splice sites, the interactions between the general splicing apparatus and its regulators are mostly unknown+ In particular, the molecular events that determine the tissue-specific use of an exon in mammalian cells have not been described+ One difficulty in understanding the precise nature of an exon's regulation is the diversity of mechanisms that can affect its splicing+ Splicing enhancer elements activate the use of splice sites that are otherwise ignored by the general splicing machinery (Hertel et al+, 1997;Wang & Manley, 1997), whereas repressor sequences are thought to block recognition of certain splice sites+ The tissue-specific expression of a particular splicing pattern often depends on a combination of positive and negative control+ Splicing enhancers can be classified by their location in either exons or introns+ These two types of enhancer are thought to be mechanistically different and to bind different types of regulatory proteins+ Exonic splicing enhancer sequences are often bound by a group of factors called SR proteins (Fu, 1995;Chabot, 1996;Manley & Tacke, 1996;Valcarcel & Green, 1996;Caceres & Krainer, 1997)+ Proteins in the SR family contain one or two RNA binding domains of the RRM type and a C-terminal domain rich in serine-arginine dipeptides+ SR proteins are essential for constitutive splicing and also play an important role in the selection of alternative splice sites+ In particular, SR proteins bound with other factors to exonic splicing enhancers are thought to promote spliceosome assembly to upstream 39 splice sites, although the mechanism for this effect on splicing is not yet clear (Wang et al+, 1995;Zuo & Maniatis, 1996; Rudner et al+, 1998)+ In contrast to ex-onic enhancers, intronic splicing enhancers are often found in introns downstream of regulated exons, and have not been shown to bind SR proteins (Balvay et al+, 1992;Black, 1992;Huh & Hynes, 1994;Del Gatto & Breathnach, 1995;Sirand-Pugnet et al+, 1995;Carlo et al+, 1996;Kawamoto, 1996;…”
Section: Introductionmentioning
confidence: 99%
“…The removal of introns in higher eukaryotes requires the assembly of the spliceosome to accurately recognize short, poorly conserved 39 and 59 splice sites (Reed & Palandjian, 1997;Burge et al+, 1999)+ The presence of weakly conserved splice sites allows extensive alternative pre-mRNA splicing to occur, one of several processes that exponentially enrich the proteomic diversity of higher eukaryotic organisms (Black, 2000;Graveley, 2001)+ Current estimates indicate that more than 60% of human genes are alternatively spliced, sometimes leading to hundreds of different mRNA isoforms from a single gene+ However, poorly conserved splice sites can lead to aberrant splicing, often compromising the expression of the correct gene products (Krawczak et al+, 1992;Nakai & Sakamoto, 1994;Carstens et al+, 1997;Lee & Feinberg, 1997;Stoppa-Lyonnet et al+, 1997)+ Based on the observation that the majority of exons are significantly shorter than introns, it has been proposed that exons are basic units of recognition in higher eukaryotes (Berget, 1995)+ Studies on regulated alternative splicing have identified exonic cis-acting elements, referred to as exonic splicing enhancers (ESEs), that facilitate the process of exon definition+ These elements are capable of activating weak splice sites in adjacent introns+ It is now appreciated that ESEs are not only components of regulated exons but also of constitutively spliced exons (Mayeda et al+, 1999;Schaal & Maniatis, 1999)+ Generally, ESEs are binding sites for members of the serine/arginine-rich (SR) protein family of essential splicing factors+ The assembled SR proteins, in turn, are thought to directly or indirectly recruit individual components of the spliceosome to the exon prior to the removal of adjacent introns (Fu, 1995;Manley & Tacke, 1996;Tacke & Manley, 1999;Blencowe, 2000;Graveley, 2000)+ The doublesex (dsx ) repeat element (dsx RE) is a well-characterized ESE consisting of six nearly identical 13-nt repeat elements that are binding sites for Transformer (Tra), Transformer 2 (Tra2), and an additional SR protein+ When fully assembled, the dsx RE complex activates the recognition of a weak, sex-specific 39 splice site (Ryner & Baker, 1991;Tian & Maniatis, 1992;Lynch & Maniatis, 1996;Tacke & Manley, 1999)+ It was demonstrated that each 13-...…”
Section: Introductionmentioning
confidence: 99%
“…SR proteins have been observed to in¯uence splicing activity via their binding to both splice sites and special splicing accessory sequences known as enhancers (Zahler et al, 1993b;Fu, 1995;Manley and Tacke, 1996;Valcarcel and Green, 1996). Recent studies have indicated substrate-speci®c binding and activity for individual SR proteins (Fu, 1993;Sun et al, 1993;Zahler et al, 1993a;Ca ceres et al, 1994;Wang and Manley, 1995;Chandler et al, 1997;Liu et al, 1998).…”
Section: Introductionmentioning
confidence: 99%